Romantic Love as Renunciation and Sacrifice: What Do Young People Think? - Bosch Fiol, Esperanza; Herrezuelo, Raquel; Ferrer Pérez, Victoria A. (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2019)
Romantic love and the myths related to it are strongly gendered, and give rise to erroneous beliefs and attitudes about the couple and their continuity that, in addition to conditioning affective relationships, have been related to the genesis and maintenance of intimate partner violence against women. Among these beliefs are those relating to the role of sacrifice and renunciation (described in Lee’s typology as Agape love style), which are considered to be an indissoluble part of the concept of romantic love, and of the traditional female gender mandate, and which may be self-limiting and constitute covert violence. In order to investigate this issue and the differences between women and men in dealing with these renunciations, a qualitative study was carried out proposing to a sample of 260 university students to assess the extent to which they would be willing to make changes in different important aspects of their lives (place of residence, employment, friendships, and life project) out of love. The results indicate that students are willing to make certain sacrifices in the name of love (especially regarding the change of residence), but not others (such as friendships), although the motivations expressed by boys and girls are different.
Keywords: romantic love; renunciation; Agape; gender; differential socialization